2015
DOI: 10.21660/2015.18.4216
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Sustainable Management Practice (Smp) Including Porous Biochar/Geopolymer Structures for Contaminated Water Remediation

Abstract: As a result of agribusiness in Australia and across the world, water is contaminated with nutrients and pesticides which threaten riverine environments, wetlands, urban drinking water supplies and also marine assets such as the Great Barrier Reef (GBR). Much can be done and sustainable management practices (SMP) can be put into place to reduce water impacts from agriculture. Required investment levels are insignificant compared to the economic advantages to be gained from adopting appropriate SMP across Austra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The materials evaluated for geopolymer development for water purification include metakaolin (Shikuku et al, 2022), volcanic ash (Tome et al, 2021), pozzolan and biochar composites (Dzoujo et al, 2022), and municipal solid waste incineration fly ash (Al-Ghouti et al, 2020) among others. For example, Craig et al (2015) reported the application of biochar/geopolymer composites in the remediation of pesticides (such as atrazine, dieldrin, picloram, metolachlor, tebuthiuron, and hexazinone) from contaminated water. Albeit little research work has been carried out on the interactions of geopolymers with pesticides in water, no research work has reported the use of municipal waste incineration fly ash (MWFA)-based geopolymers as adsorbents for endosulfan removal from contaminated water.…”
Section: Introductionmentioning
confidence: 99%
“…The materials evaluated for geopolymer development for water purification include metakaolin (Shikuku et al, 2022), volcanic ash (Tome et al, 2021), pozzolan and biochar composites (Dzoujo et al, 2022), and municipal solid waste incineration fly ash (Al-Ghouti et al, 2020) among others. For example, Craig et al (2015) reported the application of biochar/geopolymer composites in the remediation of pesticides (such as atrazine, dieldrin, picloram, metolachlor, tebuthiuron, and hexazinone) from contaminated water. Albeit little research work has been carried out on the interactions of geopolymers with pesticides in water, no research work has reported the use of municipal waste incineration fly ash (MWFA)-based geopolymers as adsorbents for endosulfan removal from contaminated water.…”
Section: Introductionmentioning
confidence: 99%
“…Degradation of water quality is one of the immediate negative impacts in Indonesia. Water pollution comes from factory sewerage [4], domestic waste [5], and pesticides from agriculture [6]. For tackling water pollution, it has been installed Waste Water Treatment Plant (WWTP) with a centralized system in Indonesia, but the WWTP was built only in 12 cities and only served 10% of Indonesia's population [7].…”
Section: Introductionmentioning
confidence: 99%
“…Six of these studies focused on freshwater and/or marine water quality at the reef catchment scale; 11−16 five studies determined the impacts and toxicity of herbicides to a range of organisms, including plants, fish, algal, coral, and seagrass; 17−21 one study assessed the role of herbicides on sustainability and water quality of forest ecosystems; 22 and another study considered the use of chemically reactive barriers for the treatment of runoff and drainage containing herbicides. 23 Some of these studies focus on PSII herbicides as a group rather than quantifying the concentration and effects of tebuthiuron as an individual herbicide. Most of the papers, particularly those relating to water quality, have monitored large areas containing multiple land uses with interpretation of tebuthiuron data from grazing inferred rather than measured directly.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A literature review using “tebuthiuron” and “Australia” in 2015 found 13 journal papers. Six of these studies focused on freshwater and/or marine water quality at the reef catchment scale; five studies determined the impacts and toxicity of herbicides to a range of organisms, including plants, fish, algal, coral, and seagrass; one study assessed the role of herbicides on sustainability and water quality of forest ecosystems; and another study considered the use of chemically reactive barriers for the treatment of runoff and drainage containing herbicides . Some of these studies focus on PSII herbicides as a group rather than quantifying the concentration and effects of tebuthiuron as an individual herbicide.…”
Section: Introductionmentioning
confidence: 99%